2021
DOI: 10.3389/fnhum.2021.617596
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Effects of Acute Aerobic Exercise Intensity on Inhibitory Control in Children With Attention Deficit/Hyperactivity Disorder

Abstract: The present study aimed to examine whether the effect of acute aerobic exercise on inhibitory control of children with attention-deficit/hyperactivity disorder (ADHD) is moderated by exercise intensity. Using a within-subjects design, 25 children with ADHD completed a flanker task with concurrent collection of electroencephalography (EEG) data after three different intensities of treadmill running. The results showed that low- and moderate-intensity exercises resulted in shorter reaction times (RTs) relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…For the studies that assessed the acute effects of interventions, 7 reported the target heart rate of their movement intervention, ranging from 50 to 80% of the suggested maximum heart rate (moderate to vigorous intensity activity; Tables 5 , 6 ). One study included three experimental groups with the target exercise heart rate of 30% (Light), 50–60% (Moderate), and 70–80% (Vigorous) of the suggested maximum heart rate, respectively ( 104 ). Two other studies reported average heart rate during/right after movement intervention (Vogt et al ( 115 ): 154.50 bpm ± 10.06; Vogt et al ( 110 ): 143.09 bpm ± 14.40; Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the studies that assessed the acute effects of interventions, 7 reported the target heart rate of their movement intervention, ranging from 50 to 80% of the suggested maximum heart rate (moderate to vigorous intensity activity; Tables 5 , 6 ). One study included three experimental groups with the target exercise heart rate of 30% (Light), 50–60% (Moderate), and 70–80% (Vigorous) of the suggested maximum heart rate, respectively ( 104 ). Two other studies reported average heart rate during/right after movement intervention (Vogt et al ( 115 ): 154.50 bpm ± 10.06; Vogt et al ( 110 ): 143.09 bpm ± 14.40; Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using EEG, several studies found changes in resting-state slow- and fast-wave activity in children with ADHD, suggesting normalized cortical arousal level after movement interventions ( 91 , 93 , 94 , 97 , 104 ). Specifically, Janssen et al (2016) found decreased theta activity over the midline regions (Fz, Cz, and Pz) after 28 physical activity training sessions ( 97 ), and Huang et al found decreased EEG theta/alpha ratios over frontal (F2, F4, Fz) and central (C3, C4, Cz) regions following an 8-week water aerobics intervention compared to a control intervention [Hedges' g = −0.63 and −0.72 (within); −0.60 and −0.61 (between)] ( 93 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations